A lifecycle estimator of intergenerational income mobility - Ursula Mello; Martin Nybom; Jan Stuhler (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
The estimation of intergenerational mobility ideally requires full income histories to determine lifetime incomes. However, as applications are typically based on shorter snapshots, estimates are subject to lifecycle bias. Using long income series from Sweden and the US, we illustrate that standard correction methods struggle to account for one important property of income processes: children from more affluent families tend to experience faster income growth, even conditional on their own characteristics. We propose a lifecycle estimator that captures this pattern and that performs well across different settings. We then apply this estimator to study mobility trends in Sweden and in the US, including for more recent cohorts that could not be considered in prior work. Despite rising income inequality, intergenerational income mobility remained largely stable over cohorts born 1950-1989 in both countries.
Keywords: J62; 330; Intergenerational mobility; lifecycle bias; income processes